RESPON PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PRE NURSARY TERHADAP PEMBERIAN PUPUK KANDANG AYAM DAN PUPUK ORGANIK CAIR - Ampuni Murnihati Hia; Razali Razali; Irwan Agusnu Putra (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2023)
Introduction: The purpose of this study was to determine the response of tomato plants (Solanum licopersicum) to the administrationof liquid organic fertilizer (poc) cow urine and phosphorus fertilizers on andisol soil. Materials and Methods: This research will be carried out in Selayang Village, Prestasi District, Langkat Regency, North Sumatra, from January to April 2023. This research used Liquid Organic Fertilizer (POC) and Chicken Manure with different doses. The design used was a Randomized Block Design (RBD) consisting of Liquid Organic Fertilizer Factors (POC) E0 = Without applying liquid organic fertilizer, E1 = 40ml/liter of water(4%), E2 =50ml/liter of water(5%) and Chicken Manure B0 = Without Chicken Manure, B1 = 100grams of Chicken Cage, B2 =200gram of Chicken Cage. The parameters observed in this study were plant height (cm), number of leaves (strands), stem diameter (mm), and leaf area (cm2). Results: The application of liquid organic fertilizer in oil palm nurseries had a significant effect on the number of leaves at 4 MST, 5 MST and stem diameter at 4 MST. The best treatment was at E1 =40ml/liter of water (4%). The application of chicken manure to oil palm nurseries did not significantly affect all parameters. The best treatment was found in treatment (B2 = 200grams of chicken coop. The interaction of liquid organic fertilizer D. grow and chicken manure had a significant effect on the number of leaves aged 4 WAP. The best treatment combination was found in treatment E2B1 (50 ml/liter of water (5%) (100 grams of chicken coop).